1976
DOI: 10.1002/dev.420090109
|View full text |Cite
|
Sign up to set email alerts
|

Audiogenic priming in DBA/2J and C57 BL/6J mice: Interactions among age, prime‐to‐test interval, and index of seizure

Abstract: C57BL/6J mice, not susceptible to audiogenic seizures (AGS) on the 1st exposure to an acoustic stimulus, were exposed to the acoustic stimulus for 1 min and then tested at some later date (acoustic priming). They were first exposed at either 8, 16, 19, 22, or 28 days of age, and then tested for AGS 2-16 days after priming. DBA/2J mice, susceptible to AGS on the 1st exposure to intense noise, were exposed to the acoustic stimulus at 26 days of age, and then again 2-14 days later. Data indicate that the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…There have been comprehensive reviews on the historical and genetic aspects of audiogenic strains of rodents, including the DBA/2 mouse [18][19][20]. The characteristics of the seizures and the particular stimuli required have been reviewed [18,21], as well as apparent biochemical, endocrine, or developmental abnormalities [22,23]. Finally, the pharmacology of audiogenic seizures has been the subject of several articles [22,[24][25][26][27][28][29][30].…”
Section: The Dba/2 Mousementioning
confidence: 99%
“…There have been comprehensive reviews on the historical and genetic aspects of audiogenic strains of rodents, including the DBA/2 mouse [18][19][20]. The characteristics of the seizures and the particular stimuli required have been reviewed [18,21], as well as apparent biochemical, endocrine, or developmental abnormalities [22,23]. Finally, the pharmacology of audiogenic seizures has been the subject of several articles [22,[24][25][26][27][28][29][30].…”
Section: The Dba/2 Mousementioning
confidence: 99%
“…The development of this response is best characterized for the C57BL/6J strain in which the magnitude of the average seizure response is dependent upon the age at 1st exposure (during which no behavioral seizure occurs) and also on the duration in days between the 1st and the 2nd acoustic challenge. Again, agreement is general that these mice are maximally sensitive t o the effects of a 1st exposure t o noise at a time coincident with the opening of the ear canal between 14 and 16 days of age, followed by decreasing sensitivity t o acoustic priming thereafter (Chen, 1973a,b;Henry, 1067;Schreiber & Graham, 1976).…”
mentioning
confidence: 72%
“…They demonstrate that the magnitude of and the time course of the effects of acoustic priming in CS7BL/6J mice are dependent not only on the age of thc niouse at priming and the duration (days) between priming and testing (Schreiber tk Graham, 1976), but also are dependent on the intensity and duration of audiogenic …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Schreiber and Graham (1976) found that the prime-to-test interval influenced the level of AGS severity displayed by C57 mice upon testing. Because the Long-Evans strain is most closely related to the Sprague-Dawley rat strain, it was hypothesized that the optimal testing day would be between postnatal Days 32 -36 (approximately 19 days after priming).…”
Section: Experiments 1: Time Of Acoustic Priming and Testing On Develomentioning
confidence: 97%